Effect of Time of Initiation of Feeding after Hatching and Influence of Dietary Ascorbic Acid Supplementation on Productivity, Mortality and Carcass Characteristics of Ross 308 Broiler Chickens in South Africa - Mbajiorgu, C.A.; Ng`ambi, J.W.; Norris, D. (International Journal of Poultry Science, 2007)
An experiment was conducted to evaluate the effect of time of initiation of feeding after hatching and influence of dietary ascorbic supplementation during realimentation on productivity, carcass characteristics and mortality of Ross 308 broiler chickens. The study was a factorial arrangement in a complete randomized design. Six hundred and seventy five unsexed Ross 308 broiler chickens with an initial weight of 32±2 g per bird were assigned to 15 treatments in a 3 (times of initiation of feeding) x 5 (ascorbic acid supplemental levels) factorial arrangement with three replications, each having 15 birds each. The experimental diets were isocaloric and isonitrogenous but with different ascorbic acid supplementation levels. Ascorbic acid supplementation started three days after hatching. More than 50% of the birds died between one and three days of age when initiation of feeding after hatching was above 36 hours. Time of initiation of feeding above 36 hours of hatching resulted in lower (p<0.05) live weight between one and three days of old. However, the birds ‘caught-up’ within ten days of realimentation. This compensatory growth could be explained in terms of increased efficiency of growth. Thereafter, ascorbic acid supplementation during realimentation lowered (p<0.05) mortality rate and improved (p<0.05) growth rates and live weight irrespective of time of initiation of feeding after hatching. Growth rate and live weight increased incrementally with increasing levels of ascorbic acid supplementation within each time of initiation of feeding after hatching in comparison with those without ascorbic acid supplementation at 21 day of age and continued until 42 days of age. Similarly, increasing ascorbic acid supplementation within each time of initiation of feeding after hatching increased dressing percentage and breast meat yield at 42 days old. However, ascorbic acid supplementation had no effect (p>0.05) on feed intake of the bird’s irrespective of time of initiation of feeding after hatching. It is concluded that time of initiation of feeding above 36 hours after hatching is not desirable, mainly because of its effect on mortality. However, the beneficial effect of ascorbic acid supplementation could be exploited in reducing mortality rate and improving growth rates in broiler chickens subjected to delayed initiation of feeding after hatching.